Cien años de lealtad: en honor a Luis Leal = One hundred years of loyalty : in honor of Luis Leal - Poot Herrera, Sara; Lomelí, Francisco A.; Herrera-Sobek, María (University of California, Santa Barbara, 2007)
V. 1. Luis Leal y los estudios literarios -- Cultura y literatura -- v. 2. Creación literaria -- Luis Leal, persona y personaje -- Luis Leal y los estudios literarios -- Cultura y literatura -- Creación literaria -- Luis Leal, persona y personaje.
Papers from a joint conference held in Nov. 2007 and organized by the University of California, Santa Barbara, Universidad Nacional Autónoma de México, Instituto Tecnológico de Monterrey and Universidad del Claustro de Sor Juana
Includes bibliographical references
Keywords: Leal, Luis -- 1907-2010 -- Congresses; Leal, Luis; Konferenzschrift -- 11.2007